Drosophila Neto is essential for clustering glutamate receptors at the neuromuscular junction. - Kim, Y.J.; Bao, H.; Bonanno, L.; Zhang, B.; Serpe, M. (Genes & Development, 2012)
Neurotransmitter receptor recruitment at postsynaptic specializations is key in synaptogenesis, since this step confers functionality to the nascent synapse. The Drosophila neuromuscular junction (NMJ) is a glutamatergic synapse, similar in composition and function to mammalian central synapses. Various mechanisms regulating the extent of postsynaptic ionotropic glutamate receptor (iGluR) clustering have been described, but none are known to be essential for the initial localization and clustering of iGluRs at postsynaptic densities (PSDs). We identified and characterized the Drosophila neto (neuropilin and tolloid-like) as an essential gene required for clustering of iGluRs at the NMJ. Neto colocalizes with the iGluRs at the PSDs in puncta juxtaposing the active zones. neto loss-of-function phenotypes parallel the loss-of-function defects described for iGluRs. The defects in neto mutants are effectively rescued by muscle-specific expression of neto transgenes. Neto clustering at the Drosophila NMJ coincides with and is dependent on iGluRs. Our studies reveal that Drosophila Neto is a novel, essential component of the iGluR complexes and is required for iGluR clustering, organization of PSDs, and synapse functionality.